Puppet Drama As an Instrument of Environmental Preservation - Oscar Echo Quiros (International Journal of Science and Society, 2019)
This document discusses the knowledge about the promotion of environmental protection through the use of puppets and simple practical tests for the first grade in rural areas in southwestern Costa Rica. Twenty-eight college students wrote a puppet show, designed and built a puppet show, held presentations, and supervised scientific experiments. The experiments tried to uncover some of the natural onions that are related to the problems in the theater work. In 2016 and 2017, a total of 334 seven-year-old students from 19 primary schools participated. Students' views and answers to questions addressed to children were included in the table by questionnaire. A retrospective linear analysis was used to establish a correlation. The data showed that children had a much better understanding of the nature and importance of protection after games and ongoing trials.